Active offer of services in Canada’s official languages: development of a patient experience questionnaire - Sauvé-Schenk, Katrine; Pignac, Sarah; Kemenade, Solange Van; Savard, Sébastien; Prud'homme, Denis; Savard, Jacinthe (Journal of Communication in Healthcare, 2026)
ABSTRACT Background: In the bilingual Canadian context, the use of a preferred official language with healthcare providers is linked to optimized communication, respectful patient-centered care, improved safety and quality of services. This study aimed to develop and test a questionnaire that measures patients’ experience of how language was considered during an outpatient health encounter. Methods: French and English questions were drafted based on a literature review. Questionnaire content and flow were validated through focus groups with experts and service users. Question understanding and clarity was verified with cognitive interviews and pre-tests with diverse service users. The final questionnaire was pilot tested in three health organizations and temporal stability, and construct validity was verified. Results: Participants were nine anglophone and eleven francophone experts and service users for the focus groups, six anglophone and six francophone service users for the cognitive interviews, eleven anglophone and ten francophone service users for the pre-test. The resulting questionnaire has 31 experience-related questions organized under six themes: arrival/greeting, interpretation and translation services, language of health services, relationship with healthcare providers, visibility of official languages and follow-up. The questionnaire is completed online in French or English. The questionnaire was pilot tested with 199 participants in three sites. Temporal stability was moderate to good. Initial evidence of construct validity was demonstrated, suggesting that the questionnaire is adequate to evaluate patient experience. Conclusion: This questionnaire is the first known bilingual patient-experience tool, focused on the active offer of services in official languages during outpatient healthcare encounters, with preliminary validation.

Prolonged Impact of the COVID-19 Pandemic on the Well-being and Roles of Family/Friend Caregivers of Older Adults Living at Home in Canadian Official Language Minority or Majority Communities - Savard, Jacinthe; Savard, Sébastien; Duong, Patrick; Hatungimana, Nelly Oriane; Benoit, Josée; De Moissac, Danielle; Dupuis-Blanchard, Suzanne; Robitaille, Annie (Canadian Journal on Aging / La Revue canadienne du vieillissement, 2026)